Pembelajaran Sains Untuk Anak Usia Dini Dengan Model Pembelajaran Sentra Bahan Alam - Erna Roostin; Mutiara Swandhina (Teknodika, 2019)
Science learning in early childhood education is a series of fun learning excitement to stimulate children to explore their environment and reflect on their observations and discoveries through science activities, it allows children to explore various objects, both living objects and lifelike objects around it. Children learn to find the symptoms of objects and the symptoms of events from these objects. Science also trains children using five of its sensing to identify different objects and symptom events.the child is trained to see, to feel, to smell, to feel and to hear. The more sensory involvement in learning, the child increasingly understands what is learned. The child acquires new knowledge of its sensing with various objects surrounding it, so that knowledge obtained will be useful as a further thought capital. natural materials center with science learning. The center of natural materials is filled with various media learning that comes from nature, such as water, sand, rocks, leaves. In the center of natural materials children have the opportunity to use natural media with various ways of playing according to the thoughts and ideas each with different results.The selected materials and tools must be safe and free from harmful toxic substances.this is also a unified approach in which children at the time are thinking and building a basic understanding of the world.The introduction of science for early childhood if done correctly will develop gradually the logical ability of the children have not been possessed.